Redesigning the relationship between heritage and city: Insights from the Gandhi Heritage Portal, Ahmedabad - Thomas, Pooja (Urban Studies, 2024)
Urban heritage is often tasked with the burden of mediating city history as well as its imagined futures. In Asian contexts, these imagined futures have often been encoded as smart' urbanity while historicity is wielded as soft power. Past studies have discussed this in the context of Ahmedabad, a significant urban centre in the region of Gujarat, India, whose urban heritage has served to promote the city's image. This article suggests that it is the digital archive, the Gandhi Heritage Portal, that potentially offers ways of disrupting the mediation of the city through heritage. With ethnographic interviews, observations, and secondary literature on the histories of the city, this article attempts a close discursive reading of the spatial, material, and ideological implications of an Ashram doing' technology through the Gandhi Heritage Portal. The article suggests that the making of the digital archive offered opportunities to dislocate heritage from neoliberal aspirations of the city.
Keywords: Digital Archive; Heritage Portal; Smart City; Urban Futures; Ahmedabad